2011
DOI: 10.1007/s12199-011-0206-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and depressive symptoms among Japanese men and women

Abstract: Objectives Evidence is limited on the relation between metabolic syndrome and depressive symptoms. The aim of this cross-sectional study was to investigate the association between metabolic syndrome and depressive symptoms in a Japanese working population. Methods The study subjects comprised 458 municipal employees (age range 21-67 years) from two municipal offices in Japan. A modified version of the criteria of the National Cholesterol Education Program Adult Treatment Panel III was used to define metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
(50 reference statements)
1
12
3
Order By: Relevance
“…However, after stratified by gender, depressive symptoms were associated with TG component only in women but not in men. Yasumi Kimura and colleagues claimed that depressive symptoms was associated with fasting hyperglycemia while Sang Jin Rhee announced that HDL component was associated with depressive symptoms in women [37, 38]. In our study, women with depressive symptoms had significantly higher value of glucose, TG and HDL components than those without them which was similar with the previous studies [37, 38].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, after stratified by gender, depressive symptoms were associated with TG component only in women but not in men. Yasumi Kimura and colleagues claimed that depressive symptoms was associated with fasting hyperglycemia while Sang Jin Rhee announced that HDL component was associated with depressive symptoms in women [37, 38]. In our study, women with depressive symptoms had significantly higher value of glucose, TG and HDL components than those without them which was similar with the previous studies [37, 38].…”
Section: Discussionsupporting
confidence: 90%
“…Yasumi Kimura and colleagues claimed that depressive symptoms was associated with fasting hyperglycemia while Sang Jin Rhee announced that HDL component was associated with depressive symptoms in women [37, 38]. In our study, women with depressive symptoms had significantly higher value of glucose, TG and HDL components than those without them which was similar with the previous studies [37, 38]. In especial, the prevalence of elevated TG in our study was dramatically higher than the other studies also held in Asia areas.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of people with schizophrenia conducted in Belgium (Vancampfort, Probst, et al, 2012) and Thailand (Suttajit & Pilakanta, 2013) and in the general populations of Japan (Sekita et al, 2013), Greece (Tziallas et al, 2012), the United Kingdom (Akbaraly et al, 2009), and Taiwan (Lin, Liang, Liao, & Tsay, 2014) have shown that very severe depressive symptoms are associated with a high risk of developing MetS. Maslov et al (2009) and Kimura, Matsushita, Nanri, and Mizoue (2011) investigated people with schizophrenia and found no correlation between depressive symptoms and MetS. Maslov et al (2009) and Sekita et al (2013) found that the number of depressive symptoms increased progressively with the number of MetS components in the general male population.…”
Section: Discussionmentioning
confidence: 99%
“…[456] In contrast, the studies which have evaluated the prevalence of MS and depression (as a disorder or as subsyndromal depression) in patients attending general hospitals or the community-based population have evaluated 215 to 6,189 subjects and have reported a prevalence rate of MS between 11.7 and 57%. [78910111213141516171819202122232425] These studies suggest that the presence of depression increases the risk of development of MS by twofold. [720]…”
Section: Introductionmentioning
confidence: 99%